The Baltic revolution : Estonia, Latvia, Lithuania, and the path to independence - Lieven, Anatol (Yale University Press, 1993)
Concealed behind the Iron Curtain, and dominated by Soviet Russia for half a century, the Baltic states of Estonia, Latvia and Lithuania have now emerged to the attention of the world as free and independent nations. As the new republics fight for political and economic viability, Anatol Lieven, the only western journalist permanently based in the Baltic during the struggle for independence, presents an intimate and engaging portrait of their history and culture, from their ancient origins to the present day. He explores the characteristics and personalities of the Baltic peoples, their religious and national differences, their relations with Russia and with the West, and their prospects for the future. The book opens with two highly entertaining chapters on the early history of the Baltic peoples, their conquest by the Christians, the evolution of the Lithuanian empire, the union with Poland, and the experience of the Baltic provinces under the Russian Empire. It then looks at the countries' first struggle for independence in 1918, the failure of democracy and the establishment of authoritarian regimes, and the Soviet annexation of the Baltic in 1940. Lieven draws a revealing portrait of the class structure of the Baltic states and the ethnic tensions that existed between the Germans, Jews, Poles and Russians who have lived there. Drawing on a wide range of sources in several languages, including interviews, newspaper accounts and his own observation, he describes and analyses the reawakening of cultural self-awareness during the late 1980s. The final section of the book examines the tumultuous years of nationalist struggle (1987-92), the constitutions of the new republics, and the results of their first free elections - in autumn 1992. Lieven comments provocatively on the fragile new order, the demolition of the Soviet economies, and the possibilities for democracy and Westernization, or for ethnic conflict and nationalist dictatorship. His sensitive, passionate and involved account provides a frank and searching exploration of the Baltic peoples and their destiny.